2017
DOI: 10.5858/arpa.2016-0501-ra
|View full text |Cite
|
Sign up to set email alerts
|

Review of Clinical Next-Generation Sequencing

Abstract: Context.-Next-generation sequencing (NGS) is a technology being used by many laboratories to test for inherited disorders and tumor mutations. This technology is new for many practicing pathologists, who may not be familiar with the uses, methodology, and limitations of NGS.Objective.-To familiarize pathologists with several aspects of NGS, including current and expanding uses; methodology including wet bench aspects, bioinformatics, and interpretation; validation and proficiency; limitations; and issues relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
195
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(225 citation statements)
references
References 121 publications
0
195
0
13
Order By: Relevance
“…While all methods have caveats and advantages to be aware of, it is also important to be aware that the data analysis pipeline is critical in any NGS platform. Both customized commercially available and in‐house analysis pipelines are commonly used . Indeed the performance of an NGS assay depends not only on the physical assay and instrumentation itself, but the computational/analytical tools being used or which have been developed.…”
Section: Dna and Rna Based Molecular Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…While all methods have caveats and advantages to be aware of, it is also important to be aware that the data analysis pipeline is critical in any NGS platform. Both customized commercially available and in‐house analysis pipelines are commonly used . Indeed the performance of an NGS assay depends not only on the physical assay and instrumentation itself, but the computational/analytical tools being used or which have been developed.…”
Section: Dna and Rna Based Molecular Assaysmentioning
confidence: 99%
“…Both customized commercially available and in-house analysis pipelines are commonly used. [58][59][60] Indeed the performance of an NGS assay depends not only on the physical assay and instrumentation itself, but the computational/analytical tools being used or which have been developed. As such, it is critical to know the weaknesses and issues with any NGS workflow.…”
Section: Illumina Sequencing Technology-sequencing By Synthesismentioning
confidence: 99%
“…Here, we applied targeted next‐generation sequencing (TGS) technology, the most available ‎and promising method available, to identify a novel, homologous mutation of CDHR1 gene in a Chinese family with autosomal recessive retinal dystrophy, extending the gene's mutation spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…CDHR1 is a photoreceptor-specific cadherin, 9 and immunoprecipitation studies showed that CDHR1 are also found in complexes with PROM1 and actin filaments, playing a critical role in photoreceptor disk morphogenesis. 10 Here, we applied targeted next-generation sequencing (TGS) technology, the most available and promising method available, [11][12][13][14][15][16] to identify a novel, homologous mutation of CDHR1 gene in a Chinese family with autosomal recessive retinal dystrophy, extending the gene's mutation spectrum.…”
mentioning
confidence: 99%
“…If the laboratory does not already perform NGS for other indications, this investment can be on the order of hundreds of thousands of dollars. 1 More ''turnkey'' solutions that include bioinformatics processing, variant annotation, and storage solutions may mitigate the investments required in these areas, but they may be limited in capability and cost more. Single biomarker tests, by contrast, performed with more traditional methodologies (eg, Sanger sequencing), require less capital investment, as the infrastructure and platforms generally exist in the laboratory.…”
mentioning
confidence: 99%